Studies on the Seeding Depths and Pre-Sowing Seed Treatments on the Seedling Emergence of Sunflowers and Safflowers - Daulay, H S; Ahuja, C P; Singh, R P (Annals of Arid Zone, 2016)
Two field experiments, one on sunflowers, (EC 68414) and the other on safflowers (A-300) were conducted on the sandy loam soils of the Central Research Farm, C. A. Z. R. I. Jodhpur. Soaked and unsoaked seeds were dibbled at depths Of 3, 5, 7 and 9 cm. The main findings of the investigations are: (i) sowing of sunflower and safflower seeds at 3 and 5 cm depths resulted in higher seedling emergence than the other depths tried (ii) soaked seeds of sunflowers and safflowers performed better at the shallower seeding depths (3 and 5 em) and (iii) from the view point of final plant stand, 5 em depth appears to be optimum for planting sunflowers and safflowers.